A utilidade da anatomia da lâmina foliar para a identificação e systemática de espécies de Bambuboideae (Poaceae, Poales) - Leandro, T. D. [UNESP]; Shirasuna, R. T.; Filgueiras, T. S.; Scatena, V. L. [UNESP] (FapUNIFESP (SciELO), 2016)
Bambusoideae is a diverse subfamily that includes herbaceous (Olyreae) and woody (Arundinarieae and Bambuseae) bamboos. Species within Bambusae are particularly difficult to identify due to their monocarpic lifecycle and the often long durations between mass flowering events; whereas the herbaceous bamboos are pluricarpic, but often are found with no reproductive structures. The leaf blade anatomy of 16 sympatric species of native Brazilian bamboos (Olyreae and Bambuseae) from the Atlantic Rainforest was studied in order to detect useful features for their identification. All the studied species share the following features: epidermis with a single stratum of cells; adaxial bulliform cells; mesophyll with arm cells, rosette cells, and fusoid cells; and collateral vascular bundles. Herbaceous bamboos share two features: papillae scattered on the abaxial surface and parallel-sided arrays of bulliform cells; whereas woody bamboos share: centrally organized papillae and fan-shaped arrays of bulliform cells. Also within the woody bamboos, intercostal fibers and a midrib with only one vascular bundle (simple midrib) characterize the subtribe Arthrostylidiinae; whereas a midrib with more than one vascular bundle (complex midrib) and a stomatal apparatus with two pappilae per subsidiary cell characterize the subtribe Chusqueinae. There are also diagnostic features for the sampled species, such as: papillae shape, and the outline and structure of the midrib. An identification key for all the studied species is provided based on the anatomical features.
The utility of Bambusoideae (Poaceae, Poales) leaf blade anatomy for identification and systematics
Keywords: Arthrostylidiinae; Bambuseae; Chusqueinae; Leaf blade; Olyreae